2022
DOI: 10.1186/s12917-022-03535-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and serological survey of paratuberculosis in cattle in selected districts of Western Uganda

Abstract: Knowledge of Mycobacterium avium subsp. paratuberculosis (MAP) herd infection status is important to plan appropriate control and prevention strategies for Paratuberculosis (PTB); however, in Uganda MAP infection status of most herds is unknown. This study aimed at determining the MAP infection status of cattle herds and the associated risk factors for MAP infection in six western districts of Uganda. The survey covered a total of 93 herds where faecal and blood samples were collected from 1814 cattle. A Recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Previous studies reported that in most countries with substantial dairy businesses, the prevalence of MAP infection at the herd level is expected to reach 50% [10]. In Western Uganda, the real animal-level prevalence was more than 3%, with a herd-level prevalence of more than 40% [11]. In Ethiopia, on the basis of the prevalence of gross lesions, the prevalence even reached 11.25% [12].…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies reported that in most countries with substantial dairy businesses, the prevalence of MAP infection at the herd level is expected to reach 50% [10]. In Western Uganda, the real animal-level prevalence was more than 3%, with a herd-level prevalence of more than 40% [11]. In Ethiopia, on the basis of the prevalence of gross lesions, the prevalence even reached 11.25% [12].…”
Section: Introductionmentioning
confidence: 95%